Maine Community Hospitals: Providing High-Quality, Affordable Care - Mayhew, Mary (Maine Policy Review, 2004)
Mary Mayhew in this commentary provides the perspective of the Maine Hospital Association in response to a study analyzing hospital costs in Maine from 1993-2003.